Effect of stacking layup on spring-back deformation of symmetrical flat laminate composites manufactured through autoclave processing - M Nasir, M Nazreen; Seman, M Adam; Mezeix, Laurent; Aminanda, Yulfian; Rivai, Ahmad; Ali, Karim Mansur (Institute of Physics Publishing, 2017)
The residual stresses that develop within fibre-reinforced laminate composites during autoclave processing lead to dimensional warpage known as spring-back deformation. A number of experiments have been conducted on flat laminate composites with unidirectional fibre orientation to examine the effects of both the intrinsic and extrinsic parameters on the warpage. This paper extends the study on to the symmetrical layup effect on spring-back for flat laminate composites. Plies stacked at various symmetrical sequences were fabricated to observe the severity of the resulting warpage. Essentially, the experimental results demonstrated that the symmetrical layups reduce the laminate stiffness in its principal direction compared to the unidirectional laminate thus, raising the spring-back warpage with the exception of the [45/-45]S layup due to its quasi-isotropic property.